Bioinspired Structural Design Enables Synergistic Toughness and Conductivity in Hydrogels for Advanced Wearable Electronics - Liu, Yi; Wang, Xuchen; Wang, Junjie; Li, Zhuang; Ao, Kelong; Liang, Guangwei; Liu, Haiqing; Zhang, Qirui; Pan, Mengjiao; Shou, Dahua (Nano-Micro Letters, 2026)
Conductive hydrogels are revolutionizing the fields of wearable sensors, implantable bioelectronics, and soft robotics. However, achieving both mechanical robustness and high conductivity within a single system remains challenging. Here, inspired by the cooperative vascular–neural networks in biological tissues, we develop a nanofiber-reinforced conductive hydrogel composed of poly(vinyl alcohol) (PVA), aramid nanofibers (ANFs), and in situ polymerized PEDOT:PSS. Through solvent- and thermally induced structural reorganization, the hydrogel evolves into a bi-continuous architecture in which the mechanical and conductive networks are intimately coupled. The tough, ANF-reinforced porous PVA mimics the vascular system, providing mechanical support and maintaining toughness, while the poly(3,4-ethylenedioxythiophene) (PEDOT) network resembles neural pathways, enabling efficient electron transport. This structural evolution enables a rare synergy of high tensile strength (10.72 MPa) and ultrahigh conductivity (452.75 S m−1) with excellent biocompatibility. The hydrogel maintains stable conduction under impact and complex deformation, supporting multimodal sensing from large-amplitude joint motion to low-amplitude electrophysiological signals: electrocardiographic and electromyographic. When integrated with a convolutional neural network, it achieves 99.54% accuracy in recognizing five complex hand gestures. This bioinspired strategy paves the way for developing robust and conductive hydrogels toward next-generation intelligent wearable electronics. Highlights: 1 A bioinspired design mimicking the cooperative vascular–neural networks in biological tissues was proposed to guide the development of conductive hydrogels. 2 Solvent- and thermally induced structural reorganization enhances poly(vinyl alcohol) crystallinity and poly(3,4-ethylenedioxythiophene) chain alignment, yielding a synergistic combination of high tensile strength (10.72 MPa) and ultrahigh conductivity (452.75 S m−1). 3 The hydrogel ensures stable electrical conduction and reliable multimodal sensing, enabling accurate and electromyographic/electrocardiographic monitoring and 99.54% gesture recognition accuracy.